Implementasi Asuhan Keperawatan Pada Ny. S Dengan Rendam Kaki Air Hangat Terhadap Kualitas Tidur Lansia - Safitri, Devi (Initium Medica Journal, 2021)
Sleep quality is a person’s satisfaction with sleep, so that the person does not show feelings of tiredness, irritability and anxiety, lethargy and apathy, blackness at the glance of the eyes, swollen eyelids, red conjunctiva, sore eyes, headaches and often yawning or drowsiness. Scientific Writing This profession aims to carry out Nursing Care in Mrs. S With Soaking Feet Warm Water Against Elderly Sleep Quality in Hot Spring Community Health Work Areas in 2018 and held on October 15, 2018 until October 17, 2018. The method used in this Professional Scientific Writing is a case study conducted based on the stages of care nursing includes the assessment, diagnosis, intervention, implementation, evaluation of nursing. Professional Scientific Writing Results obtained 1 nursing diagnosis, namely sleep quality disorders associated with headaches. Nursing evaluation showed that there was an improvement in sleep quality after being given a warm water bath for 3 days, on the second day the patient said that he slept well and was a little fresh when he woke up in the morning. Through the Puskesmas, it is hoped that it can provide a penkes about soaking warm feet in patients with sleep quality disorders